The Curitiba government's politeness strategies on Facebook - Traesel, Francieli Aparecida (2015)
The purpose of this article is to reflect upon the role of Politeness and Social Media in Public Communication. From this on, we carry out a qualitative analysis, by describing and interpreting the politeness strategies used in the interaction between Curitiba’s Local Authority Facebook and population on June 8th 2014 "Plantão Curitiba" post. This post refers to the heavy rains that hit Southern Paraná in the period. The model for politeness strategies analysis we chose is Brown & Levinson's (1987), one of those added to Pragmatics theories. As a result of this study, we state that when the organization is defending from FTAs, it appeals to negative politeness strategies - the most impolite of them, excuses, are the furthest ones from public communication principles. Excuses, even though they may be used to avoid conflicts in interactions, considering it is a public organization, it can let people think that their point of view has been ignored, making worse a not so good image of the organization. On the other hand, when it uses positive politeness strategies, seeks agreement, shows interest in people's opinion and involvement. Using digital media as a way of interaction strategy shows that, several times, there are conficts which wouldn't reach the same extent when covered by traditional media, and it's because of their own characteristics. We put politeness forward as a way of establishing interactions guidelines likely to result in a good relationship between public organization and citizens.